Biotechnological advancements enabling cannabinoid biosynthesis in engineered fungi: a mini review - Manganyi, Madira Coutlyne; Kaptchouang Tchatchouang, Christ Donald (Frontiers in Fungal Biology, 2025)
Cannabinoids, such as Δ9tetrahydrocannabinol (THC) and cannabidiol (CBD), are bioactive compounds with well-documented therapeutic potential, including applications in pain relief, neuroprotection, anti-inflammatory treatments, and seizure control. Traditionally sourced from Cannabis plants, their production remains limited by agricultural constraints, regulatory hurdles, and environmental concerns. In response, recent advances in biotechnology have enabled the microbial biosynthesis of cannabinoids, offering a scalable and sustainable alternative. Engineered fungi, in particular, have gained attention as promising production platforms due to their metabolic flexibility, ease of genetic manipulation, and capacity for synthesizing complex secondary metabolites. This mini-review explores key innovations in synthetic biology and metabolic engineering that have enabled fungal cannabinoid biosynthesis. It highlights strategies such as pathway reconstruction, enzyme optimization, host strain engineering, and the application of CRISPR-Cas9 genome editing. In addition, it examines ongoing challenges, including product toxicity, metabolic burden, and regulatory considerations. Finally, the review outlines future directions in systems biology, the production of rare cannabinoids, and bioprocess optimization. Overall, the development of engineered fungi for cannabinoid biosynthesis represents a major conceptual advance in microbial biotechnology, with far-reaching implications for the pharmaceutical, nutraceutical, and industrial sectors.